1981
DOI: 10.1007/bf00278696
|View full text |Cite
|
Sign up to set email alerts
|

Partial 11q trisomy syndrome

Abstract: The syndrome caused by partial trisomy for 11q is reviewed on the basis of a patient of our own and 20 cases (including a stillbirth) from the literature. The main symptoms are presented in Tables 1 and 2. The syndrome can be suspected when, in addition to mental retardation, the following characteristics are present: short nose, long philtrum, micrognathia, retracted lower lip, and micropenis in males. In 15 families, the mother was a balanced translocation carrier and in four the father. The translocation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…Francke et al [1977] from their analysis of 13 published cases with 11q trisomy suggested that 11q partial trisomy causes a specific well recognized duplication 11 (q21 $ q23 to qter) syndrome. Pihko et al [1981] in their review of 21 cases with partial 11q trisomy confirmed this observation. They have suggested that 11q partial syndrome can be suspected when the patient have a short nose, long philtrum, low set ears, micrognathia, retracted lower lip, clavicular defect, and micropenis in males, in addition to mental retardation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Francke et al [1977] from their analysis of 13 published cases with 11q trisomy suggested that 11q partial trisomy causes a specific well recognized duplication 11 (q21 $ q23 to qter) syndrome. Pihko et al [1981] in their review of 21 cases with partial 11q trisomy confirmed this observation. They have suggested that 11q partial syndrome can be suspected when the patient have a short nose, long philtrum, low set ears, micrognathia, retracted lower lip, clavicular defect, and micropenis in males, in addition to mental retardation.…”
Section: Discussionsupporting
confidence: 63%
“…Although constitutional partial trisomy is well described in the literature [Francke et al, 1977;Pihko et al, 1981], this partial trisomy is always accompanied with a partial monosomy of the other chromosome involved in the translocation. Francke et al [1977] from their analysis of 13 published cases with 11q trisomy suggested that 11q partial trisomy causes a specific well recognized duplication 11 (q21 $ q23 to qter) syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…However, duplications have been reported much less frequently for segments from 11q13.3 to 11q23 [Schinzel, 2001]. In most of the reported cases other chromosomes have been involved making it difficult to determine the effect of the 11q partial trisomy [Lurie et al, 1979;Pihko et al, 1981;de France et al, 1984;Zhao et al, 2003]. A total of seven cases of isolated 11q duplication with no other chromosomal involvement have been reported.…”
Section: Introductionmentioning
confidence: 92%
“…11,[19][20][21][22][23] Similarly, a shorter segment involving 11q13 → qter band found in a RCT has been observed. [24][25][26] Meiotic segregation pattern To identify the various possible genetic imbalances that can be produced by carriers of chromosomal translocations, the meiotic segregation patterns in sperm cells can be evaluated. To date, the meiotic segregation patterns in sperm cells from 4200 different RCTs have been studied.…”
Section: Discussionmentioning
confidence: 99%